Pengembangan Aplikasi Ujian Fisika Berbasis Komputer untuk Meningkatkan Integritas Peserta Didik di SMA Islam Assa’adah - Khaerul Fuad; Irnin Agustina Dwi Astuti; Indica Yona Okyranida (UNIVERSITAS INDRAPRASTA PGRI, 2021)
This study aims to develop a computer-based exam application using a template from the BeeSMART CBT application. The research method used in this research is a research and development method with the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). This research has produced a computer-based exam application. Validation test results, this application is suitable for use. The average total score for the material expert validation assessment was 93.75%, and the total score average was 90.44% for the media expert validation assessment with each score included in the